Measuring the impact of household energy consumption on respiratory diseases in India - Mohammad Ahmad Faizan; Ramna Thakur (BMC, 2019)
Abstract Background Most households in developing countries like India are not able to afford to get the services of efficient energy for cooking and lighting. Therefore, they rely mostly on solid fuels (firewood, dung cakes, crop residue, coal/coke/lignite). Such fuels cause respiratory diseases like tuberculosis, asthma respiratory cancer. Hence, this study aims to estimate the association between different types of energy used and the prevalence of respiratory diseases in India where more than 50% of the population relies on solid fuels for cooking. Methods The study is based on 117,752 respondents who were diagnosed with various chronic diseases such as diabetes, chronic heart diseases, leprosy, chronic renal diseases, tuberculosis, asthma etc. from District Level Household Survey (DLHS-4) which was conducted in 2012-13. Individuals who were diagnosed with a chronic illness after a proper medical examination have been considered as a dependent variable. Exposure to the type of cooking fuel is the main exposure variable, which recognises the dependence on energy. Logistic regression has been utilized to understand the association between the use of solid fuels for cooking and the prevalence of respiratory diseases. Results The dependence on solid fuels is very high in rural areas (72.22%) as compared to urban areas (21.43%). Among different castes, the reliance on solid fuels for cooking is highest among Scheduled Castes (61.79%) and Scheduled Tribes (70.46%). Individuals living in households where crop residue and coal/lignite is used for cooking suffer from asthma/chronic respiratory failure in the higher proportion as compared to others. Results further revealed that the use of solid fuels for cooking has a strong association with respiratory diseases. Individuals living in households where solid fuels like firewood [OR: 1.27 (0.001); C.I.: 1.19-1.35], crop residue [OR: 1.33 (0.001); C.I.:1.19-1.48], and coal [OR: 1.60 (0.001); C.I.:1.32-1.93] are used as primary fuel for cooking are 17 to 60% more likely to suffer from respiratory diseases. Conclusion Use of solid fuels is associated with respiratory diseases like asthma, tuberculosis and cancer of the respiratory system. Assuming these associations are causal, therefore, about 17 to 60% of the respiratory diseases in India could be prevented by providing access to clean cooking fuel to the individuals.